A randomised trial of ondansetron for the treatment of irritable bowel syndrome with diarrhoea. Issue 10 (12th December 2013) - Garsed, Klara; Chernova, Julia; Hastings, Margaret; Lam, Ching; Marciani, Luca; Singh, Gulzar; Henry, Amanda; Hall, Ian; Whorwell, Peter; Spiller, Robin
Abstract : Background: Irritable bowel syndrome with diarrhoea (IBS-D) is particularly debilitating due to urgency and episodic incontinence. Some 5-hydroxytryptamine 3 (5-HT3) receptor antagonists (5-HT3RAs) have proven effective but have serious side effects. Ondansetron, also a 5-HT3RA, has been widely used as an antiemetic with an excellent safety record for over two decades. Our aim was to assess its effectiveness in IBS-D. Methods: 120 patients meeting Rome III criteria for IBS-D entered a randomised, double-blind, placebo-controlled crossover study of 5 weeks of ondansetron 4 mg versus placebo with dose titration allowed, up to two tablets three times daily in the first 3 weeks. Patients completed daily diaries documenting stool consistency using the Bristol Stool Form score. Gut transit was measured in the last week of each treatment. The primary endpoint was average stool consistency in the last 2 weeks of treatment. Results: Ondansetron significantly improved stool consistency (mean difference in stool form between ondansetron and placebo −0.9, 95% CI −1.1 to −0.6, p<0.001). Compared with placebo, patients on ondansetron experienced fewer days with urgency (p<0.001), lower urgency scores (p<0.001), reduced frequency of defaecation (p=0.002) and less bloating (p=0.002), although pain scores did not change significantly. IBS symptom severity score fell more with ondansetron than placebo (83±9.8 vs 37±9.7, p=0.001). 65% reported adequate relief with ondansetron but not placebo compared with 14% reporting relief with placebo but not ondansetron, relative risk 4.7, 95% CI 2.6 to 8.5, p<0.001. Conclusions: Ondansetron relieves some of the most intrusive symptoms of IBS-D, namely loose stools, frequency and urgency.